Por que pensar sobre a autorreferencialidade em pintura hoje? (Revista Apotheke, 2017)
This article aims to show how the study of the self-referentiality of painting allowed me to reflect on my own work and on issues related to figurative painting today.
Keywords: painting; Self-referentiality; Representation